2017
DOI: 10.1016/j.jallcom.2016.09.178
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric properties and thermal conductivity of core-shell structured Ni@NiO/poly(vinylidene fluoride) composites

Abstract: To suppress the high loss of nickel (Ni)/poly(vinylidene fluoride) (PVDF) while remaining high dielectric constant (k) near the percolation threshold. In this study, core-shell structured Ni (Ni@NiO) particles were prepared by heat treatment of raw Ni powder under air atmosphere and incorporated into PVDF to prepare Ni@NiO/PVDF dielectric composites. The morphological, dielectric properties and thermal conductivity of the composites are characterized. The results indicate that compared with the raw Ni reinforc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
57
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(57 citation statements)
references
References 27 publications
0
57
0
Order By: Relevance
“…The effect of filler addition in enhancement of dielectric permittivity of different polymers can be perceived from Table . In general, pristine PI is used as a polymer matrix because it has good mechanical properties, in addition to high chemical and thermal stability, but the dielectric constant ε ≈ 3.5, and the dielectric permittivity has been several times enhanced (28.42 times, 26.6 times, 4 times, and 50 times) by incorporating various form of CCTO, BT, and other core/shell fillers. In the last section, significance and advantages of MAM technique have been presented; Y. Zhan et al applied this remote‐controlled alignment technique to align the surface modified BN/Fe3O4/PDA in PEN matrix.…”
Section: Role and Effect Of Filler/hybrid Filler Addition On Dielectrmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of filler addition in enhancement of dielectric permittivity of different polymers can be perceived from Table . In general, pristine PI is used as a polymer matrix because it has good mechanical properties, in addition to high chemical and thermal stability, but the dielectric constant ε ≈ 3.5, and the dielectric permittivity has been several times enhanced (28.42 times, 26.6 times, 4 times, and 50 times) by incorporating various form of CCTO, BT, and other core/shell fillers. In the last section, significance and advantages of MAM technique have been presented; Y. Zhan et al applied this remote‐controlled alignment technique to align the surface modified BN/Fe3O4/PDA in PEN matrix.…”
Section: Role and Effect Of Filler/hybrid Filler Addition On Dielectrmentioning
confidence: 99%
“…Nano‐Ag powder has been utilized as a third phase reinforcement with BT, and L. Zhang et al concluded that silver added 3 phase composites (PVDF/BaTiO 3 /Ag) exhibited 2 times better dielectric constant than 2 phase composites. In order to improve the dielectric constant, incorporation of fillers in the form of core and shell was followed; ie, X. Kuang et al used Ag@c (silver‐core and carbon‐shell) fillers and amalgamated in the PVDF matrix to achieve better dielectric constant. Various techniques have been used to prepare ceramic fillers such as sol‐gel method, hydrothermal method, etc.…”
Section: Role and Effect Of Filler/hybrid Filler Addition On Dielectrmentioning
confidence: 99%
“…This mainly relies on the phonon conduction due to atoms and molecules that collide with each other ; thus, the degree of crystallization has a significant effect on thermal conductivity. In addition, other factors such as the morphology , dispersion filler shape and size , and interaction between the two phases , also have certain effects on thermal conductivity and thermal diffusion properties.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3] PDNs can be induced not only by directly tensile, 4,5 but also by compounding PVDF with other conductive fillers, such as copper nanowire (CuNWs), silver (Ag). [1][2][3] PDNs can be induced not only by directly tensile, 4,5 but also by compounding PVDF with other conductive fillers, such as copper nanowire (CuNWs), silver (Ag).…”
Section: Introductionmentioning
confidence: 99%